Magnitude effects for experienced rewards at short delays in the escalating interest task - Young, Michael E.; Webb, Tara L.; Sutherland, Steven C.; Jacobs, Eric A. (My University, 2012)
A first-person shooter video game was adapted for the study of choice between smaller sooner and larger later rewards. Participants chose when to fire a weapon that increased in damage potential over a short interval. When the delay to maximum damage was shorter (5 – 8 s), people showed greater sensitivity to the consequences of their choices than when the delay was longer (17 – 20 s). Participants also evidenced a magnitude effect by waiting proportionally longer when the damage magnitudes were doubled for all rewards. The experiment replicated the standard magnitude effect with this new video game preparation over time scales similar to those typically used in nonhuman animal studies and without complications due to satiation or cost.
Keywords: Judgment and decision making; Choice behavior; Impulsivity; Delay discounting